In Vitro and In Vivo Efficacy of Novel Flavonoid Dimers against Cutaneous Leishmaniasis - Wong, Iris L. K. (American Society for Microbiology, 2014)
Treatment of leishmaniasis by chemotherapy remains a challenge because of limited efficacy, toxic side effects, and drug resistance. We previously reported that synthetic flavonoid dimers have potent antipromastigote and antiamastigote activity against Leishmania donovani, the causative agent of visceral leishmaniasis. Here, we further investigate their leishmanicidal activities against cutaneous Leishmania species. One of the flavonoid dimers (compound 39) has marked antipromastigote (50% inhibitory concentrations [IC(50)s], 0.19 to 0.69 μM) and antiamastigote (IC(50)s, 0.17 to 2.2 μM) activities toward different species of Leishmania that cause cutaneous leishmaniasis, including Leishmania amazonensis, Leishmania braziliensis, Leishmania tropica, and Leishmania major. Compound 39 is not toxic to peritoneal elicited macrophages, with IC(50) values higher than 88 μM. In the mouse model of cutaneous leishmaniasis induced by subcutaneous inoculation of L. amazonensis in mouse footpads, intralesional administration of 2.5 mg/kg of body weight of compound 39.HCl can reduce footpad thickness by 36%, compared with that of controls values. The amastigote load in the lesions was reduced 20-fold. The present study suggests that flavonoid dimer 39 represents a new class of safe and effective leishmanicidal agent against visceral and cutaneous leishmaniasis.